Stratifikasi Risiko Kematian Jantung Mendadak pada Sindrom Koroner Akut - Jusup Endang; Dewi H Suprobo; Radityo Prakoso; Yoga Yuniadi; Bambang B Siswanto; Nani Hersunarti (The Indonesian Heart Association, 2013)
Sudden cardiac death is the leading cause of cardiovascular mortality in acute coronary syndrome. Risk stratification scoring tools are available to better identify patients at risk after acute myocardial infarction. In addition plenty of factors and treatment modalities modulate the risk of sudden cardiac death.A case of in-hospital SCD in a young woman with acute anterior STEMI is presented as a trigger to the importance of risk stratification and treatment according to guidelines in preventing SCD.